The Effectiveness of Using Booklet Media on Increasing Women's Knowledge and Attitudes Regarding Premenopause - Wa Ode Hajrah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Many women experience premenopausal syndrome almost all over the world. Symptoms felt by premenopausal women can be a problem in dealing with menopause. Most women think restless when facing menopause; so many simple problems become so big and even make a woman despair when facing menopause. A booklet is printed media in the form of a small book that can be used to provide health education, especially regarding premenopausal syndrome. This study aimed to determine the effect of booklet media on women's knowledge and attitudes about premenopausal syndrome at the Koja District Health Center. The research method used is a quasi-experimental design with one group pretest-posttest. A total of 42 women were given an intervention using the media booklet. The results showed that booklet media could increase women's knowledge (p = 0.0001) and attitudes (p = 0.0001) about the menopausal syndrome. It can be concluded that the media booklet has an effect on increasing women's knowledge and attitudes about premenopausal syndrome at the Koja District Health Center.